Hormonal therapy after the operation for catamenial pneumothorax – is it always necessary?. Issue 1 (December 2016) - Subotic, D.; Mikovic, Z.; Atanasijadis, N.; Savic, M.; Moskovljevic, D.; Subotic, D.
Abstract Background Our recent clinical observations put into question the routine hormonal therapy for pneumothorax recurrence prevention, in patients operated for catamenial pneumothorax (CP). Methods Retrospective review of the treatment of four women operated for CP in a recent 32-months period. Results The four presented patients with CP represent 4.8 % of the overall number of patients operated for spontaneous pneumothorax and 19 % of women operated for pneumothorax in the same period. In all patients, typical multiple diaphragm holes existed. The involved part of the diaphragm was removed with diaphragm suture in three patients, whilst in one patient, a diaphragm placation was done. Endometriosis was histologically confirmed in two patients. During the follow-up period of 6–43 months, none of the patients underwent a postoperative hormonal therapy for different reasons, and in none of them the pneumothorax recurrence occurred. Conclusion The clinical course of these patients, with the absence of the pneumothorax recurrence despite the omission of the hormonal treatment, suggests that the appropriateness of the routine hormonal treatment with gonadotrophin-releasing hormone analogues for 6–12 months, should be reconsidered and re-evaluated in further studies.